Dual regulation of gastrointestinal tumor progression by the IFN-γ/STAT1 pathway and prospects for targeted therapy - Liu, Yuhao; Huang, Yuxin; He, Qiaoying; Shen, Yuyan; Wang, Yaoling (Frontiers in Oncology, 2025)
Gastrointestinal malignant tumors exhibit a high incidence and mortality rate among all malignancies worldwide, making them a significant concern within the field of oncology. Targeted therapy for gastrointestinal tumors has become a hot topic in recent years, and its specific mechanism remains to be further elucidated. Secreted factors, including cytokines, chemokines, and growth factors, as components of the tumor microenvironment, play a crucial role in the progression of gastrointestinal tumors. Interferon-gamma (IFN-γ) can activate these factors through JAK1/2 and STAT1 signaling (the IFN-γ/STAT1 pathway). This pathway is considered “a double-edged sword” and maintains a dual role in promoting or inhibiting tumor progression by activating different downstream factors. In this review, we summarize the functions, mechanisms, and key factors of the IFN-γ/STAT1 pathway that promote or inhibit gastrointestinal tumor progression and discuss therapeutic prospects for targets of the pathway.